Mechanical behaviour of compacted kaolin clay stabilised via alkali activated calcium-rich fly ash binder. (December 2022) - Coudert, Elodie; Russo, Giacomo; Deneele, Dimitri; Tarantino, Alessandro
Abstract: Locally sourced marginal earthfill geomaterials are generally not used in traditional earthfill construction due to their relatively poor mechanical performance. However, if these geomaterials are stabilised, procuring and transporting of materials from borrow sites can be avoided with significant carbon saving. Further carbon saving can be achieved by using industrial waste as binder in place of conventional high-carbon footprint stabilisers such as lime and Ordinary Portland Cement. This paper examines the use of a calcium-rich fly ash from coal combustion activated by a sodium-based alkaline solution for the treatment of non-active clay in view of its use as earthfill geomaterial. To this end, kaolinite clay/fly ash (90/10) samples were compacted, cured for different periods, saturated, and subjected to one-dimensional compression and direct shear tests. The major outcome from 1D compression tests is that stiffness is enhanced significantly even in the very short-term (1 day after alkali activation), i.e. before the binding phase starts to form. This was attributed to the changes in pore-water chemistry (increase in pH and electrolyte concentration) following the addition of the alkaline solution and the formation of aggregates in face-to-face mode. In the long term (curing time ≥ 28 days) stiffness appeared to be further enhanced due to the formation of the binding phase. These effects were more pronounced in the low-intermediate stress range (< ∼ 700 kPa) making the alkali activation a good soil treatment for roadway embankments. Peak shear strength also appeared to be significantly enhanced in both short and long term although effects were more pronounced for curing time ≥ 28 days following the formation of the binding phase. Ultimate shear strength is enhanced only in the long term (curing time ≥ 28 days). Highlights: Carbon saving can be achieved by using industrial waste as binder in place of conventional binders. Alkali-activated fly ash from coal combustion has been used as binder for soil stabilisation. Compacted saturated treated samples were subjected to 1D compression and direct shear tests. Stiffness is enhanced in the very short-term due to formation of aggregates in face-to-face mode. Peak shear strength also appeared to be significantly enhanced in both short and long term.